How news affects sectoral stock prices through earnings expectations and risk premia - Anna Kirstine Hvid; Kristian Loft Kristiansen (European Central Bank (ECB), 2020)
A growing body of literature analyses the impact of news on companies' equity prices. We add to this literature by showing that the transmission channel of news to prices differs across sectors. First, we disentangle sectoral equity prices into components of expected future earnings and equity risk premia. Then, we evaluate how these react to general and sector specific sentiment shocks constructed from Reuters news articles. We find that price changes for especially the financial sector are mainly driven by changes in equity risk premia, while changes in earnings expectations play a comparatively larger role for other sectors.
Keywords: G10; G12; G14; 330; Text analysis; news sentiment; stock returns; equity risk premia; Dividend Discount Models